Oat Plant Amyloids for Sustainable Functional Materials. Issue 4 (20th December 2021) - Zhou, Jiangtao; Li, Ting; Peydayesh, Mohammad; Usuelli, Mattia; Lutz‐Bueno, Viviane; Teng, Jie; Wang, Li; Mezzenga, Raffaele
Abstract: Amyloid functional materials from amyloid fibril building blocks, produced in vitro from amyloidogenic natural proteins or synthetic peptides, show diverse functionalities ranging from environmental science and biomedicine, to nanotechnology and biomaterials. However, sustainable and affordable sources of amyloidogenic proteins remain the bottleneck for large‐scale applications, and to date, interest remains essentially limited to fundamental studies. Plant‐derived proteins would be an ideal source due to their natural abundance and low environmental impact. Hereby oat globulin, the primary protein of oat plant ( Avena sativa ), is utilized to yield high‐quality amyloid fibrils and functional materials based thereof. These fibrils show a rich multistranded ribbon‐like polymorphism and a fibrillization process with both irreversible and reversible pathways. The authors furthermore fabricate oat‐amyloid aerogels, films, and membranes for possible use in water purification, sensors, and patterned electrodes. The sustainability footprint of oat‐amyloids against other protein sources is demonstrated, anticipating an environmentally‐efficient platform for advanced materials and technologies. Abstract : Plant‐derived protein is an ideal source to scale‐up amyloid‐material applications due to their natural abundance and low environmental impact. Hereby, the authors found oat globulin could yield high‐quality amyloid fibrils, showing multistranded ribbon‐like polymorphism and both irreversible and reversible fibrillization pathways. The authors anticipate these sustainable oat‐amyloids would be an environmentally‐efficient platform for advanced materials.